2019
DOI: 10.1029/2018jb016167
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resolution of the Subducting Plate Interface in Central Alaska From Autocorrelation of Local Earthquake Coda

Abstract: Subducting plates below 10‐km depth are primarily imaged using phases from teleseismic earthquakes at frequencies dominantly below 1 Hz, resulting in low‐resolution images compared to fault zone thickness. Here we image the plate boundary zone in Alaska using scattered body wave arrivals in local earthquake coda to produce a higher‐resolution image of the slab. An autocorrelation method successfully extracts coherent arrivals from the local earthquake signals. Our autocorrelation results image interfaces assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 47 publications
2
23
1
Order By: Relevance
“…Correspondingly, the large historical earthquakes along the Alaska subduction interface yield to a general pattern that strike‐slip earthquake (i.e., 2018 Mw 7.9 Gulf of Alaska earthquake) occurred outlier ocean plate, large shallow thrust‐slip (purple region of 1964 Mw 9.2 Alaska) occurred in boundary between upper intracrustal and ocean plate, and normal slip in the deep ocean plate, as shown in Figure . The Anchorage earthquake sustains the results of seismic image from previous results (Eberhart‐Phillips et al, ; Kim et al, ). On the other hand, earthquakes in subduction zones can be divided into intracrustal thrust event and intraoceanic strike‐slip/normal event (Krabbenhoeft et al, ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Correspondingly, the large historical earthquakes along the Alaska subduction interface yield to a general pattern that strike‐slip earthquake (i.e., 2018 Mw 7.9 Gulf of Alaska earthquake) occurred outlier ocean plate, large shallow thrust‐slip (purple region of 1964 Mw 9.2 Alaska) occurred in boundary between upper intracrustal and ocean plate, and normal slip in the deep ocean plate, as shown in Figure . The Anchorage earthquake sustains the results of seismic image from previous results (Eberhart‐Phillips et al, ; Kim et al, ). On the other hand, earthquakes in subduction zones can be divided into intracrustal thrust event and intraoceanic strike‐slip/normal event (Krabbenhoeft et al, ).…”
Section: Discussionsupporting
confidence: 82%
“…A clear subduction structure can help us to understand the tectonic activities beneath the Anchorage. With the autocorrelation of local earthquake coda, an enhanced resolution of the subducting plate interface in the Central Alaska was proposed in Figure (after Kim et al, ). Beneath the Anchorage region, the intracrustal thickness is ~30 km from both Slab2 (Hayes et al, ) and seismic image (Kim et al, ), in which the slow slip events and tectonic tremor have been observed by GPS and seismic data (e.g., Fu et al, ; Wech, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This earthquake occurred near the western boundary of the subducting Yakutat slab inferred by Eberhart‐Phillips et al (). The teleseismic receiver function and migration (Y. Kim et al, ), the double‐difference relocated seismicity (J. Li et al, ), and the newly autocorrelation analysis of local earthquake coda (D. Kim et al, ) depicted that the subducting Yakutat slab in this area has a thickness of ~20 km and the intraslab seismicity mostly occurred in it. In addition, according to the profile locations in their results, the Anchorage earthquake seems to occur in the flat subduction area of the Yakutat/Pacific slab.…”
Section: Discussionmentioning
confidence: 99%
“…This method, called RFs, removes complexities associated with earthquake rupture and sourceside propagation using deconvolution, thereby isolating subreceiver structure (Burdick & Langston, 1977). Typical P-to-S teleseismic RFs are analyzed and filtered in a way that makes it difficult to resolve structures that are smaller than~2 km (e.g., Kim et al, 2019); however, comparison with ground-truth well estimates show that high frequency RFs can constrain shallow structures at scales smaller than <500 m (Leahy et al, 2012). Furthermore, Audet (2010) showed that power spectral density (PSD) of RFs can even resolve temporal variations in crustal velocity structure following the 2004 Parkfield (M w 6) earthquake, constraining S-wave velocity changes of~0.06 km/s.…”
Section: Methodsmentioning
confidence: 99%